Regional variation in the elasticity of supply of housing, and its determinants: The case of a small sparsely populated country - Elias Oikarinen; Risto Peltola; Eero Valtonen (Aboa Centre for Economics (ACE), 2014)
Previous empirical investigations provide evidence of substantial regional variation in the supply elasticity of housing, and show that the elasticity and its variation across cities within the U.S. are significantly influenced by regulatory supply constraints, city level population, population density, and geographic constraints. This paper studies empirically if these findings apply to a country that is notably different from the U.S. with respect to its population density, typical city size, geographic and cultural coherence, and regulatory constraints, i.e., Finland. Based on data for the period 1987-2011, our findings are largely in line with those reported for the U.S. The results support the theoretical models indicating that the supply elasticity is largely a local phenomenon, i.e., dependent mainly on city specific factors rather than the abundance of undeveloped land at the country level. The long-term supply elasticity substantially varies across Finnish cities. The city size, zoning policies, and geographic constraints are found to be the most important factors causing regional elasticity differences, accounting for some 80% of the elasticity variation.
Keywords: R31; R52; 330; housing; supply; price; elasticity; regions